Study on the supporting performance of concrete filled steel tube arches with three different cross-sections. (June 2022) - Mei, Yu-chun; Liu, Jun-feng; Li, Wei-teng; Li, Yuan-zhen; Li, Ting-chun; Wang, Gang; Sun, Bing-jun; Zhang, Shuo
Abstract: At present, there are a variety of concrete-filled steel tube (CFST) supporting arches with different cross-sections, but a method for selecting a section that fits the site conditions is still lacking. In this paper, laboratory tests and numerical tests were carried out, and three mechanical conditions, the local compression-bending loads, the simplified ideal global loads and the simulated arch-rock contact loads, were investigated for the three most commonly used cross-section types, namely circular, square and D-shaped cross-sections. For the local compression-bending capacity, the axial bearing capacities of D-shaped cross-section specimens are 1.45% and 4.58% higher than those of the circular and square cross-section specimens, respectively; the bending bearing capacities of the square cross-section specimens are 11.19% and 22.13%/21.27% (D-shaped specimens under reverse eccentric compression) higher than those of the circular and D-shaped cross-section specimens, respectively. For the simplified ideal global loads, the straight-leg arches with square, circular and D-shaped cross-sections have bearing capacities from high to low, while the order of the bearing capacities is circular, square and D-shaped for circle arches; the difference values are not more than 10%. For the simulated arch-rock contact loads, the bearing capacities of the D-shaped type arches are 12.42% and 5.89% higher than those of the circular and square arches, respectively, under the full contact condition; the stress distribution of the surrounding rock is irregular, the stress concentration phenomenon appears near the cavity under the non-full contact condition, and the square cross-section arches have better bearing capacity behaviour with cavity widening. Finally, suggestions for the cross-section selection of the CFST supporting arch are proposed according to the quantitative test data and combined with the processing technique, production cost, construction technique and connecting joint property.